Estampes Belges - Geerinckx, Brigitte; Rouir, Eugène (Brussel : Galerie Patrick Derom, 1995)
Albert, Jos ; Berchmans, Emile ; De Bruycker, Jules ; De Groux, Henry ; De Smet, Gustave ; Delvaux, Paul ; Ensor, James ; Evenepoel, Henri ; Finch, Alfred William ; Jespers, Floris ; Khnopff, Fernand ; Lemmen, Georges ; Minne, George ; Minne, Joris ; Rassenfosse, Armand ; Rops, Félicien ; Smits, Jakob ; Tytgat, Edgard ; de Woestyne, Gustave Van ; Van Rysselberghe, Theo ; Van Straten, Henri ; Wouters, Rik
biografie
Frans
Nederlands
Estampes Belges / Belgische Grafiek, Galerie Patrick Derom Brussel, 14.11 - 30.12.1995
boek
Keywords: België